Study on Mechanical Properties of Tropical Timber Hardwood Species: Promoting Javanese Inferior Timbers for Traditional Wooden Houses - Yulianto P. Prihatmaji; Akihisa Kitamori; Satoru Murakami; Kohei Komatsu (Masyarakat Peneliti Kayu Indonesia, 2012)
Recent earthquake hitting Java Island in Indonesia has caused many damaged to Javanese wooden houses, including Joglo-type building. The Traditional wooden houses use Teak wood or locally known as Jati (Tectona grandis) and Nangka wood (Artocarpus heterophyllus) as the primary construction material for both building structure and ornaments. Repair or reconstruction of the damaged house needs the same wood material (Teak wood) in order to get the same strength, durability, and prestige. Unfortunately, obtaining Teak wood in sufficient size is difficult because of limited quantity and very expensive price. Therefore, promoting substitute wood material having similar mechanical properties to Teak wood is needed. To understand the mechanical properties of timber for Javanese timber house, compression test, three point bending test, four point bending test and four point shear test were carried out in radial and tangential direction.In this paper, authors showed substitute wood materials for avanese timber houses from tropical timber. A total of 840 specimens made from 9 tropical timber species were tested. All tropical timber specimens showed that the MOE (Modulus of elasticity) had strong relationship with density. There was a clear trend that smaller density indicated smaller MOE. Yield stress described strong relationship with densities. From all specimens tested, shear modulus, shear strength and MOR showed quite strong relationship with densities. In terms of shear modulus, Acacia, Jati and Nangka had quite similar mechanical properties. For shear strength, Nangka closely resembled Jati while glued-Acacia had equal mechanical properties to Jati in terms of MOR.